ASSISTANCE IN CREATING INNOVATIVE TECHNOLOGY-BASSED LEARNING MEDIA FOR ELEMENTARY SCHOOL TEACHERS - Ayi Abdurahman; Setiwati Setiwati; Sri Erwini Christine; Wiwin Winarni (Community Development Journal : Jurnal Pengabdian Masyarakat, 2024)
Rapid technological advancements have highlighted the importance of integrating innovative digital tools into education, particularly at the elementary level. However, many teachers face challenges in leveraging technology due to limited training and resources, resulting in a reliance on traditional teaching methods that may not engage students. This community service activity aims to empower elementary school teachers by helping them create innovative technology-based learning media tailored to the needs of their classrooms. The community service program uses a Participatory Action Research (PAR) approach, which involves a cyclical process of planning, acting, observing, and reflecting. Teachers participate in workshops to learn practical skills in designing digital teaching tools, such as interactive presentations, gamified learning resources, and digital storytelling. They then implement these tools in their classrooms, followed by a reflection session to assess effectiveness and identify areas for improvement. The community service results showed significant improvements in teachers’ ability to design and integrate technology-based learning media, which increased student engagement and participation. Teachers also reported increased confidence in using digital tools and formed peer support networks to maintain and expand their skills. In conclusion, this program successfully addressed the challenges of technology integration in elementary education by equipping teachers with practical skills and developing a collaborative learning environment. Future initiatives should focus on scaling up the program and addressing infrastructure challenges to maximize its impact.